(untitled) - Mutavhatsindi, Hygon

Evaluation of host biosignatures for targeted screening for tuberculosis at the point of care, and monitoring of the response to TB treatment (Stellenbosch : Stellenbosch University, 2020, 2020)
Thesis (PhD)--Stellenbosch University, 2020.